Impact of a Vendor-Developed Opioid Clinical Decision Support Intervention on Adherence to Prescribing Guidelines, Opioid Prescribing, and Rates of Opioid-Related Encounters - Pierce, Robert P.; Eskridge, Bernie; Ross, Brandi; Wright, Matthew; Selva, Thomas (Applied Clinical Informatics, 2022)
Background Provider prescribing practices contribute to an excess of opioid-related deaths in the United States. Clinical guidelines exist to assist providers with improving prescribing practices and promoting patient safety. Clinical decision support systems (CDSS) may promote adherence to these guidelines and improve prescribing practices. The aim of this project was to improve opioid guideline adherence, prescribing practices, and rates of opioid-related encounters through the implementation of an opioid CDSS.Methods A vendor-developed, provider-targeted CDSS package was implemented in a multi-location academic health center. An interrupted time-series analysis was performed, evaluating 30 weeks pre- and post-implementation time periods. Outcomes were derived from vendor-supplied key performance indicators and directly from the electronic health record (EHR) database. Opioid-prescribing outcomes included count of opioid prescriptions, morphine milligram equivalents per prescription, counts of opioids with concurrent benzodiazepines, and counts of short-acting opioids in opioid-naïve patients. Encounter outcomes included rates of encounters for opioid abuse and dependence and rates of encounters for opioid poisoning and overdose. Guideline adherence outcomes included rates of provision of naloxone and documentation of opioid treatment agreements.Results The opioid CDSS generated an average of 1,637 alerts per week. Rates of provision of naloxone and opioid treatment agreements improved after CDSS implementation. Vendor-supplied prescribing outcomes were consistent with prescribing outcomes derived directly from the EHR, but all prescribing and encounter outcomes were unchanged.Conclusion A vendor-developed, provider-targeted opioid CDSS did not improve opioid-prescribing practices or rates of opioid-related encounters. The CDSS improved some measures of provider adherence to opioid-prescribing guidelines. Further work is needed to determine the optimal configuration of opioid CDSS so that opioid-prescribing patterns are appropriately modified and encounter outcomes are improved.
Keywords: clinical decision support system; electronic health record; opioids; quality improvement